Brazilian normative data for the Short Form 36 questionnaire, version 2 - Josué Laguardia; Mônica Rodrigues Campos; Claudia Travassos; Alberto Lopes Najar; Luiz Antonio dos Anjos; Miguel Murat Vasconcellos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
METHODS: The study Pesquisa Dimensões Sociais das Desigualdades (PDSD) (Social Dimensions of Inequalities) involves 12,423 randomly selected Brazilian men and women aged 18 years old or more from urban and rural areas of the five Brazilian regions, and the information collected included the SF-36 as a measure of health-related quality of life. This provided a unique opportunity to develop age and gender-adjusted normative data for the Brazilian population. RESULTS: Brazilian men scored substantially higher than women on all eight domains and the two summary component scales of the SF-36. Brazilians scored less than their international counterparts on almost all of SF-36 domains and both summary component scales, except on general health status (US), pain (UK) and vitality (Australia, US and Canada). CONCLUSION: The differences in the SF-36 scores between age groups, genders and countries confirm that these Brazilian norms are necessary for comparative purposes. The data will be useful for assessing the health status of the general population and of patient populations, and the effect of interventions on health-related quality of life.